2002
DOI: 10.1016/s0006-3495(02)75603-8
|View full text |Cite
|
Sign up to set email alerts
|

Light-Induced Hydrolysis and Rebinding of Nonisomerizable Bacteriorhodopsin Pigment

Abstract: Bacteriorhodopsin (bR) is characterized by a retinal-protein protonated Schiff base covalent bond, which is stable for light absorption. We have revealed a light-induced protonated Schiff base hydrolysis reaction in a 13-cis locked bR pigment (bR5.13; lambda(max) = 550 nm) in which isomerization around the critical C13==C14 double bond is prevented by a rigid ring structure. The photohydrolysis reaction takes place without isomerization around any of the double bonds along the polyene chain and is indicative o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 31 publications
0
14
0
1
Order By: Relevance
“…To shed further light on the effect of retinal isomerization and the photocycle on the light effect, we studied artificial pigments derived from 13-cis (3)-locked [or all-trans (2)-locked] retinals (Scheme 1), where the critical C 13 AC 14 isomerization is blocked by a 5-membered ring structure (24,25). I-V characteristics similar to those obtained with apo-membranes with retinal oxime are found for those artificial pigments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To shed further light on the effect of retinal isomerization and the photocycle on the light effect, we studied artificial pigments derived from 13-cis (3)-locked [or all-trans (2)-locked] retinals (Scheme 1), where the critical C 13 AC 14 isomerization is blocked by a 5-membered ring structure (24,25). I-V characteristics similar to those obtained with apo-membranes with retinal oxime are found for those artificial pigments.…”
Section: Resultsmentioning
confidence: 99%
“…Artificial pigments were prepared by reconstituting the apomembrane (suspension in water) with trans-locked and 13-cislocked retinal analogs (24,25), respectively. Briefly, reconstitution was performed by the addition of 25-28 nmol of the retinal analogs and dissolved in 5-10 l of 2-propanol, to yield a 1-ml aqueous suspension of 32 nmol of apo-membrane.…”
Section: Methodsmentioning
confidence: 99%
“…To shed further light on the effect of retinal isomerization and the photocycle on the light effect, we studied artificial pigments derived from 13-cis-(or all-trans)-"locked" retinal, [44] in which the critical C 13 C 14 isomerization is blocked by a fivemember ring structure. [44] Structures of native all-trans retinal and the "locked" analogues used in this study are shown in Scheme 1.…”
Section: Characteristics Of Optoelectronic Responses and Transmembranmentioning
confidence: 99%
“…[44] Structures of native all-trans retinal and the "locked" analogues used in this study are shown in Scheme 1. As shown in Figure 10 (A and B), no photoeffect is seen within experimental error (typically around ± 0.1 nA for a stable junction).…”
Section: Characteristics Of Optoelectronic Responses and Transmembranmentioning
confidence: 99%
“…11 The effects of the osmotically active solutes on the PM structure have been previously studied by applying an osmotic pressure that can withdraw the aforementioned water molecules from the protein interior, distort the protein landscape, and therefore, alter the local environment and the chromophoreprotein interactions. 66,67 As shown in Figure 4a, a solution of 33% regenerated pigment (A 33% , AOO) in phosphate buffer, l max 557 nm, exhibits a monophasic positive CD at 547 nm; however, upon centrifugation and resuspension of the precipitated pellet in 50% sucrose, the CD undergoes a sign inversion exhibiting a single negative CE at 592 nm (under both conditions, the UV -vis is maintained at 561 nm; data not shown). The CD curves in buffer and sucrose can be reversibly interchanged upon repetition of the centrifugation/resuspension sequence, confirming reversible conformational changes upon solute-induced distortion.…”
mentioning
confidence: 90%